2018
DOI: 10.1177/0300060518765324
|View full text |Cite
|
Sign up to set email alerts
|

Acute chemotherapy-induced nausea and vomiting in children with cancer: Still waiting for a common consensus on treatment

Abstract: Chemotherapy-induced nausea and vomiting (CINV) is one of the most common treatment side-effects, and remains a significant concern, in children undergoing chemotherapy. Although adult patients receive chemotherapy regimens combined with appropriate standardized antiemetic treatment, children can receive markedly varying antiemetic treatments. A narrative review of CINV was performed regarding CINV definition, scoring system, prevention and treatment, specifically focussing on studies conducted with paediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 42 publications
0
27
0
4
Order By: Relevance
“…The two most commonly reported symptoms are nausea and vomiting 3. Nausea is a subjective experience characterised by a feeling of impending vomiting,5 whereas vomiting is defined as retching and expulsion of the stomach’s contents through the mouth accompanied by shivering and salivation 5. A previous study indicated that these two symptoms affected up to 70% of children undergoing chemotherapy 6.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The two most commonly reported symptoms are nausea and vomiting 3. Nausea is a subjective experience characterised by a feeling of impending vomiting,5 whereas vomiting is defined as retching and expulsion of the stomach’s contents through the mouth accompanied by shivering and salivation 5. A previous study indicated that these two symptoms affected up to 70% of children undergoing chemotherapy 6.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of nausea and vomiting in children with cancer is multifactorial,9 but it is generally believed to be largely related to chemotherapy, which is the most common type of treatment for childhood cancer 5. Chemotherapeutic agents circulating in the blood stimulate the chemoreceptor trigger zone and result in acute nausea and vomiting 10.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations